Soil organic carbon stocks of German salt marshes: a comparative study along Baltic Sea and North Sea - Logemann, Ella; Gösele, Clarisse; Nicol, Kathryn; Jensen, Kai; Müller, Peter (PANGAEA, 2025)
In order to assess the differences in soil organic carbon (SOC) stocks between contrasting geomorphological settings of salt marshes in Germany, three distinct salt marsh types were sampled: Baltic Sea salt marshes, North Sea mainland salt marshes and North Sea island salt marshes. 14 study sites were sampled between 2021 and 2022 covering gradients of different plant communities and management types. The sampled transects of the North Sea salt marshes spanned all three vegetation zones: pioneer zone, low marsh, and high marsh. In each of the 14 study sites, 8-12 plots were assessed. For the quantification of SOC content, soil bulk density and SOC δ13C signature, a single 1-m soil core was taken from each plot. An Eijkelkamp peat sampler was used for taking soil cores. Dry soil bulk density was calculated from sample dry weight and volume. Prior to elemental and isotope analysis, macroscopic root residues were removed and soil samples were acidified.
Keywords: Baltic Sea; blue carbon; carbon stocks; grazing; North Sea; Salt marshes; succession